Current Status of Fasciolosis of Goat in Sylhet, Bangladesh: An Integrated Morphomolecular Study - Chamali Akter Shykat; Saiful Islam; Foyez Ahmed; Kazi Mehetazul Islam; Jamal Uddin Bhuiyan; Tilak Chandra Nath (Journal of Parasitology Research)
Epidemiological information and proper identification of Fasciola species present in Bangladesh are important for control. This study was aimed at determining the prevalence of liver fluke infection of goats in Sylhet, Bangladesh, and identifying those using integrated morphometric and molecular techniques. A total of 260 slaughtered goats (Capra hircus) were examined, and flukes were collected from infected liver using sterilized forceps. Fasciolosis prevalence in goats was 35.38% (92/260) across all age and sex categories. Female goats were found more infected (37.14%, 65/175) than male goats (31.76%, 27/85), while infection rate was found higher in young animals (37.91%, 69/182) compared to adults (29.48% 23/78). Infection rate was observed higher in rainy season (52.96%, 45/85), followed by winter (27.38%, 26/95) and summer (26.25%, 21/80). Collected flukes were examined by light microscopy after being stained with Semichon’s acetocarmine, and sequences of mtDNA Cox1 genes were obtained. Ten adult flukes were measured, 38.72±3.37 mm in length and 11.8±1.9 mm in width. Based on morphometric features especially branching of the testis and body length/body width ratios (3.28±0.42), the flukes were primarily identified as Fasciola gigantica. Amplicon sequences were compared by BLAST and the cox1 sequences showed 97.1-99.3% similarity with the reference sequences (F. gigantica and Fasciola sp.) from GenBank. In this study, we found a considerable prevalence of fascioliasis in goats, and F. gigantica was solely identified with variation. To control these parasites and prevent potential public health risks, appropriate control techniques must be developed.